Effect of ageing on selected salivary chemical compositions and dental caries experience among group of adults - Hiba K. Al-Tamimi; Nadia A. Al-Rawi (College of Dentistry/ University of Baghdad, 2019)
Background: Ageing is a continuous accumulative ordinary physiological phenomena occurs upon all organs and body structures including saliva by its constituents which can influence the caries process, for that this study was conducted to determine the impact of ageing on selected chemical composition of saliva and their effects on dental caries experience characteristics at different age groups among apparently healthy men. Materials and method: A descriptive comparative study was conducted to compare between three study samples (young, middle and old age adults), thirty male in each study insert, aged (20 years, 40 years and 60 years) respectively. They were selected from private health center in Baghdad - Iraq, from the mid of November 2017until the end of February 2018, where they subjected to complete body investigations to confirm their health status, followed by thorough general body history and oral examination. Caries experience was recorded according to the criteria of WHO in1987. Un-stimulated saliva was collected according to Navazesh and Kumer and analyzed chemically to determine the level of calcium ions and alkaline phosphatase. All data then statistically analyzed by using SPSS version 22. Results: The current study, showed that the caries experience represented by DMFs increased with increasing age, by which the highest mean value of DMFs was established in the oldest age (60.37± 31.39) and the lowest mean value was noted among the youngest age (7.27±8.02). A significant differences existed between all study samples (p≤0.05). However, the missing surfaces represented the largest proportion of DMFs value when compared to Ds and Fs among all ages Iin the current study, with significant differences (p≤0.05) was followed by the decay fraction that found to be increased with age but with no significant difference. Salivary Calcium ions showed decreasing with increasing age with statically significant differences among different study samples while salivary alkaline phosphatase was increased with increasing age with no significant differences. Concerning the caries experience among the study samples, the salivary Ca+2 ions inversely correlated while alkaline phosphates correlated positively with caries experience. Conclusion: there is a significant age related changes on the selected chemical constituents of saliva that could affect the caries experience